Religiosity and Risky Behaviors among Adolescents Living With HIV in Southwest Nigeria - Sodeinde, Kolawole; Akadri, Adebayo; Adepoju, Akinmade; Oluwole, Temitayo; Bamidele, Olabisi; Abiodun, Olumide (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Risky behaviors remain highly prevalent among adolescents,and theyarethe foremost cause of unplanned pregnancies, sexually transmitted infections (STIs) including HIV, intellectual deterioration, and suicide attempts.Religion has been opined tomitigate risky behaviorsamong young people.This study assessed if there is arelationship between religiosity and risky behaviors among adolescents living with HIV in southwest Nigeria. It is adescriptive cross-sectional study of 212 adolescents selected via a multistage sampling technique. Data were collected using interviewer-administered questionnaires. Religiosity was classified as low, moderate,and high religious involvement based on the frequency of religious activities attendance using the Duke University Religion Index. Data was analyzed using SPSS version 22. Logistic regression was used to find factors associated with risky behavior. P was set as < 0.05.Low religiosity (OR=23.975; 95% C.I=2.591-221.851), late adolescence (OR=10.404; 95% C.I = 2.259-47.918) and not having formal education (OR=3.558; 95% C.I=1.324-9.562) significantly predicted high-risk behavior. High religiousinvolvementshold some promise in mitigating risky sexual behaviors among adolescents with HIV.Keywords: HIV/AIDS, Religiosity, Risky behavior.